Napięcie między wyborem bogactwa lub ubóstwa w perspektywie królestwa Bożego (Łk 18, 18-30) - Ćwikła, Jarosław (Poznańskie Studia Teologiczne, 2018)
In Gospel of Luke there are a number of critical statements about rich people. The third Evan- gelist wrote down, for example: [God] sent the rich away with empty hands (Lk 1: 53). But how terrible for you who are rich now, you have had your easy life ( Lk 6: 24). The third Evangelist wrote down not only single, critical sentences about the rich, but exten- sive excerpts. He enrolled for example: the text of the greed (Lk 12: 13-21), the parable about the rich man and Lazarus (Lk 16: 19-31) the text of a great feast (Lk 14: 15-24) and the text of rich man (Lk 18: 18-30). The last one, namely text of rich man (Lk 18: 18-30) focuses on the ability to make choices in the perspective of the kingdom of God. It is a sharp rebuke directed to the rich. Luke in this text warned the rich, that the penalty for them for their sinful choices in temporality, will be eternal damnation. In this article was analyzed this text.